Sosialisasi Teknologi Informasi dalam Peningkatkan Kinerja Manajemen SDM di Koperasi Jasa Keuangan Syariah di Kelurahan Limau Manis Selatan Kecamatan Pauh Kota Padang - Meswantri, Meswantri; Diana, Yusvi; Hadi, Febri (LPPM Universitas Dharma Andalas, 2024)
. This Community Service Activity is proposed as a form of implementing science to the community to handle various problems. The aim of community service activities carried out at the Sharia Financial Services Cooperative in Limau Manis Selatan Village, Pauh District, Padang City is to improve the quality of Human Resources (HR) performance in managing Cooperative activities. This goal was achieved because many staff in the cooperative were still unable to play the role of technology in supporting operational activities. The service method is carried out with an approach to implementation activities that includes the scope of implementation and work procedures. The results of the service activities that have been carried out are the application of information and communication technology to cooperative activities which will play a role in facilitating the process of implementing activities. Innovation is carried out with the aim of balancing and keeping up with current developments. The contribution of this service activity has an impact on the cooperative being more effective and efficient in management and improving HR performance